Analisis Pengaruh Variabel Makroekonomi dan Kebijakan Relaksasi Loan to Value, Terhadap Penyaluran Kredit Pemilikan Rumah Pada Bank Umum Di Provinsi Nusa Tenggara Timur - Rei, Elkostalia; Ballo, Fransina W.; Kiak, Novi Theresia (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to assess the long-term and short-term impacts of inflation, economic growth, BI Rate, and the LTV Relaxation Policy on the distribution of KPR to commercial banks in the NTT province. To achieve this, we employ quantitative analysis methods that examine the relationships between variables. Specifically, we utilize quantitative time series data, which document the periodic development of information. The data used encompasses economic growth, BI Rate, homeownership credit distribution, and inflation from 2016 to 2023. For data analysis, we employ the Vector Error Correction Model (VECM) using the EViews 12 program tool. The findings of this research reveal that, in the long term, inflation and the BI Rate have a negative and significant impact on KPR distribution in the NTT Province. Conversely, economic growth and the LTV variable have a positive, yet insignificant, effect on mortgage distribution in the long term. In the short term, the LTV variable demonstrates a positive and significant impact on KPR distribution, while economic growth and inflation show a positive but insignificant effect. Moreover, in the short term, the BI Rate exhibits a negative and insignificant impact on KPR distribution in the NTT Province. Overall, factors such as inflation, interest rates, economic growth, and LTV policy exhibit varying influences on the distribution of KPR credit, with notable disparities in the short term and long term.